International Law Analysis of Espionage at Sea and China’s Response - Liu, Chuyan (International Journal of Social Sciences and Public Administration, 2025)
Maritime espionage is a violation of international morality. In terms of the regulation of maritime espionage, there is a legal predicament at the theoretical level, with a lack of corresponding treaty law, international customary law, and international judicial precedents. At the international practice level, although all countries have domestic legislation against espionage, they hold an "ambiguous" double standard towards maritime espionage in international practice. Secondly, the principle of jurisdiction of the flag state and state immunity also bring certain difficulties to the law enforcement actions for regulating maritime espionage. This paper studies the constituent elements of maritime espionage and the legal predicament of regulating maritime espionage, aiming to provide suggestions for improving the security defense legal mechanism for regulating maritime espionage in China.